قياس الأداء المتميز للمؤسسات من خلال نماذج الجوائز العالمية للجودة - كواشي, مراد (Recherches économiques et managériales; مجلد 14 (2013): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE))
الملخص تُواجه مؤسسات اليوم تحديات كبيرة مما يُحتم عليها الوقوف على أدائها للكشف عن قدراتها وقيمتها التنافسية وموقعها في السوق، وهذا سعيًا منها لبلوغ مستوى التميز في الأداء. وعليه سنحاول من خلال هذه الدراسة التطرق إلى أهم الجوائز العالمية للجودة ومدى إسهامها في قياس التميز في أداء المؤسسات، حيث سنركز على جائزة مالكولم بالدريج للجودة والجائزة الأوروبية للجودة، وذلك على الرغم من وجود عدد كبير من الجوائز على المستوى العالمي. وعُذرنا في ذلك هو أن هاتين الجائزتين تُعدان الأشهر على الإطلاق على المستوى العالمي، كما أنهما تُمثلان المرجعية الأساسية التي تم الاعتماد عليها في تصميم بقية جوائز الجودة. Summary Institutions face significant challenges today than of having to stand on the performance of the detection capabilities and value and competitive position in the market, and this in an effort to reach a level of excellence in performance. Therefore we will try through this study to address the most important international quality awards and extent of its contribution to the measure of excellence in the performance of institutions, where we will focus on Malcolm Baldrige quality award and the European quality award, in spite of the presence of a large number of awards at the global level. This is because these awards represent the basic reference that has been reliable in the design of the rest of the quality awards.